A comprehensive musculoskeletal and peripheral nervous system assessment of war-related bilateral upper extremity amputees. Issue 1 (December 2016) - Allami, Mostafa; Mousavi, Batool; Masoumi, Mehdi; Modirian, Ehsan; Shojaei, Hadi; Mirsalimi, Fatemeh; Hosseini, Maryam; Pirouzi, Pirouz
Abstract Background Upper limb amputations are one of the unpleasant war injuries that armed forces are exposed to frequently. The present study aimed to assess the musculoskeletal and peripheral nervous systems in Iraq-Iran war veterans with bilateral upper extremity amputation. Methods The study consisted of taking a history and clinical examinations including demographic data, presence and location of pain, level of amputation, passive and active ranges of movement of the joints across the upper and lower extremities and spine, manual palpation, neurological examination, blood circulation pulses and issues related to a prosthetic limb. In this study, 103 Iranian bilateral upper extremity amputees (206 amputations) from the Iran-Iraq war were evaluated, and a detailed questionnaire was also administered. Results The most common level of amputation was the finger or wrist level (108, 52.4 %). Based on clinical examination, we found high frequencies of limited active and passive joint range of movement across the scapula, shoulder, elbow, wrist and metacarpophalangeal, interphalangeal and thumb joints. Based on muscle strength testing, we found varying degrees of weakness across the upper limbs. Musculoskeletal disorders included epicondylitis (65, 31.6 %), rotator cuff injury (24, 11.7 %), bicipital tendonitis (69, 33.5 %), shoulder drop (42, 20.4 %) and muscle atrophy (19, 9.2 %). Peripheral nerve disorders included carpal tunnel syndrome in 13 (6.3 %) and unilateral brachial plexus injury in 1 (1 %). Fifty-three (51.5 %) were diagnosed with facet joint syndrome at the level of the cervical spine (the most frequent site). Using a prosthesis was reported by 65 (63.1 %), both left and right sides. The back was the most common site of pain (71.8 %). Conclusion The high prevalence of neuro-musculoskeletal disorders among bilateral upper extremity amputees indicates that they need regular rehabilitation care.